Utilising Digital Technology for Garment Longevity - Wetherell, Sophie V; Shilton, Lucie; James, Alana (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
This research explores methods for repurposing both physical resources and contextual specialist knowledge, offering insights that can inspire and enhance future fashion design and re-manufacturing and archival practices within the industry. It questions whether digital fashion design tools, such as CLO3D can expand from facilitating faster production and consumption to enhancing the use and potential longevity of garments. The study employs an ethnographic approach to practice-based research, where the authors focus on the interaction between the physical and digital worlds, to understand the wider application of CLO3D that promotes the value and lifespan of a garment. Two case studies were investigated to explore the impact of CLO3D on longevity: a historical garment archive that examined historic pattern cutting approaches; a contemporary collection of 30 deadstock sportswear garments. This research aims to enhance the designers understanding and accessibility of archival and